2013
DOI: 10.1021/cr300367d
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarbons for the Development of Advanced Catalysts

Abstract: 1. Introduction 2. Synthesis of Novel Nanostructured Carbon Materials 2.1. Carbon Nanotubes 2.2. Graphene 2.3. Ordered Mesoporous Carbon 2.4. Carbon Hierarchy 2.5. Macroscopic Shaping of Nanocarbon 3. Functionalization of Nanocarbon Materials 3.1. Liquid-Phase Functionalization of Nanocarbon 3.2. Gas-Phase Functionalization of Nanocarbon 4. Characterization and Modeling 4.1. Characterization of Carbon 4.1.1. Microcalorimetry 4.1.2. Temperature-Programmed and Ambient Pressure Photoelectron Spectroscopy 4.1.3. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
777
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,205 publications
(792 citation statements)
references
References 421 publications
(634 reference statements)
4
777
0
11
Order By: Relevance
“…In recent years, metal oxides supported on clay, 1-3 silica [4][5][6][7] or carbon [8][9][10] materials have received enormous attention in various fields including heterogeneous catalysis. Among them, silica-supported iron oxide has been intensively studied for wastewater treatment such as degradation of organic dyes through Fenton-like reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal oxides supported on clay, 1-3 silica [4][5][6][7] or carbon [8][9][10] materials have received enormous attention in various fields including heterogeneous catalysis. Among them, silica-supported iron oxide has been intensively studied for wastewater treatment such as degradation of organic dyes through Fenton-like reactions.…”
Section: Introductionmentioning
confidence: 99%
“…2f). Additionally, dangling bonds located at the edge of sp 2 nanocarbons after saturation by hydrogen can act as high-energy sites and catalytic centers for many acid-base or redox reactions [123]. It was demonstrated that graphene edges showed a two-time higher ORR reactivity, a 4 orders of magnitude larger specific capacitance, and a faster electron-transfer rate than basal planes (Fig.…”
Section: Defect-induced Charge Transfermentioning
confidence: 99%
“…The results indicated that the presence of PEDOT on graphene matrix exhibited 6 times improvement on the oxidation peak current for urea at PEDOT-RGO composite. The higher electrocatalytic current response of the PEDOT-RGO composite than that of the RGO lm was presumably caused by a more favorable electrochemical environment for urea on the electrode [39]. PEDOT:PSS chains can be assembled onto the surfaces of RGO sheets throughstacking interactions between both components [40,41].…”
Section: Electrocatalytic Oxidation Of Urea Atmentioning
confidence: 99%